Application of rhizobacteria inoculants in biocontrol of Bacterial wilt (Ralstonia solanacearum) in potato (Solaum tuberosum) production. - Aguk, J.; Schulte-Geldermann, Elmar; Karanja, K.; Kinyua, Z.M.; Jefwa, J.M.; Parker, M. (2014)
Bacterial wilt is an important soil borne disease that threatens potato production. It is difficult to control due to the large number of hosts, high genetic and phenotypic variability of the pathogen, systemic localization of the pathogen, and lack of chemical control. Use of antagonistic microorganisms is critical due to their role in suppressing pathogenic infection. The objective of this study was to evaluate the effectiveness of three rhizobacteria isolates in suppressing of bacterial wilt on potato (cv. Tigoni and clone 387164.4). Potatoes were planted under controlled condition in complete randomized block design with 11 treatments: Azoctobacter, Bacillus and Pseudomonas as single, double and triplicate combinations, three organic amendments of poultry, cattle and compost manure and untreated control. Except for single Azoctobacter treatment all the microbial treatments and poultry manure suppressed bacterial wilt infection, reducing area under the disease progress curve by 13-40 compared to control with 53. Triple inoculation of Pseudomonas+Bacillus+Azoctobacter and duo inoculants of Bacillus+ Azoctobacter and Pseudomonas+ Azoctobacter had significantly (P<0.05) higher tuber weight of 362-418g compared to control with 143g. Apparently healthy tubers from Pseudomonas+Bacillus+Azoctobacter in clone 387164.4 were free from latent infection. There was however, no effect of the microbial inoculants and organic amendments on small and medium tuber grades and on tuber phosphorus content. These microbial inoculants were effective as biocontrols under controlled condition but more studies need to be undertaken to ascertain their effectiveness.